Editorial: Between Tradition and Modernity (Al-Jamiah: Journal of Islamic Studies, 2011)
The relationship between religious âtraditionâ and âmodernityâ is a central theme in various academic debates. Of the heatedly debated topic is concerning religious identity in the face of constantly political, economical, and global changes. As with other religious communities, Muslims have to response to these changes, on the one hand, and to the call for preserving their religious identity, on the other.